THE USE OF THE GATB AND THE AIA TESTS IN PREDICTING SUCCESS IN COURSES IN ACCOUNTING. - Beamer, George C.; Rose, Tom (The Accounting Review, 1955)
Abstract The article focuses on the General Aptitude Test Battery (GATB) and the American Institute of Accountants (AIA) tests in predicting success in courses of accounting. Attracting persons who are capable of achieving success in the field of accounting is of concern to the members of the accounting profession, schools of business and vocational counselors. Very often students and vocational counselors have little understanding of the work which an accountant does, often confusing the work with that of book keeping or routine office work. At North Texas State College an attempt is being made to discover students capable of achieving success in the field of accounting. These students may fall into one of three categories, based upon scores made on certain selected tests namely, those who are capable and are at present majoring in the subject, those who are not capable and are planning to major in the field and those who are capable of majoring in the profession but are not aware of their aptitudes. Two tests developed in recent years, are called the GATB and the other developed by the AIA, offer to counselors the possibility of selecting students who will be successful in the field of accounting.